Isolation and Characterization of Microsatellite Markers for Soybean Looper (Lepidoptera: Noctuidae). Issue 5 (31st October 2019) - Silva, C S; Cordeiro, E M G; Corrêa, A S
Abstract: We constructed 13 microsatellite markers for Chrysodeixis includens (Walker), a serious crop pest in the Americas. All SSR (Simple Sequence Repeat) markers were polymorphic, with no evidence of linkage disequilibrium between any loci in any population. The total number of alleles per locus ranged from 5 for L3, L9, and L11 to 26 for L6; the mean number of alleles per locus in three populations of C. includens ranged from 2.33 for L3 to 14.67 for L6. Hardy–Weinberg equilibrium (HWE) deviation was not observed in four loci for at least one population (L3, L5, L9, L10). Markers L6, L7, L8, L10, L11, L12, and L13 showed a frequency of null alleles > 0.2 for at least one population. STRUCTURE and F -statistics revealed low population structure among the populations ( F ST = 0.013) and a high degree of inbreeding ( F IS = 0.658). The SSR markers developed here will be useful in future studies on the ecology, demography, host dynamics, and gene flow of C. includens . This information is essential to understand the recent status of C. includens as a key pest in South America.